The Leverage–Profitability Puzzle Resurrected - Eckbo, B Espen; Kisser, Michael (Review of Finance, 2021)
Abstract With zero capital structure rebalancing costs, dynamic trade-off theory predicts that firms stay at their leverage targets with more profitable firms staying at higher leverage. This prediction is rejected by the robustly negative correlation between leverage and profitability. When rebalancing costs are added to this theory, it predicts a positive leverage–profitability correlation only in periods where companies pay these costs and actively rebalance their capital structures. However, we show that the correlation is negative when firms issue debt and distribute the proceeds to shareholders—precisely the case where the theory predicts it should be positive. Our results thus resurrect the leverage–profitability puzzle.